Rot Fungi of Cucumis Sativus (Cucumber) and their Susceptibility to Extracts of Moringa Oleifera Leaves and Allium Sativum Bulbs - Sobowale, A. A.; Ali, O. O.; Oyewole, B. O.; Elum, C. G. (European Journal of Applied Sciences, 2022)
The fungitoxic capabilities of extracts of Moringa oleifera leaves and Allium sativum bulbs against fungi associated with rot of Cucumis sativus L. (cucumber) was investigated. The rotting fruits were purchased from some markets and isolation and identification of pure cultures of fungi from the rotting cucumber fruits was done using standard procedures. Leaves of M. oleifera and cloves of A. sativum were procured and crude extracts (aqueous and ethanol) of the plant materials were obtained following standard procedures. Fungitoxic abilities of leaves of the M. oleifera and cloves of A. sativum extracts on the isolated fungi were evaluated in vitro at concentrations of 25%, 50%, 75% and 100%. The interactive impacts of the extracts on the isolated fungi was also evaluated. The experiment was carried out in triplicates. All Petri plates were incubated at 28±2oC and observed for 7 days. Diametric and radial growth measurement of the resulting fungi was taken at 24 hours intervals. Data were analysed using the GLM procedure of SAS (version 9.1). Means were separated using DMRT (p≤0.05). Isolated fungi were identified as Fusarium verticillioides, F. oxysporum and Colletotrichum orbiculare. Extract of M. oleifera gave a better growth inhibition compared to that of A. sativum in the individual assay. Combined extracts of A. sativum (50%) and M. oleifera (100%) as well as A. sativum (75%) and M. oleifera (100%) gave better growth inhibition compared to other treatment combinations. Both aqueous and ethanol extracts of A. sativum and M. oleifera significantly (p≤05) inhibited mycelia growth of the isolated fungi at different concentrations compared to control. The aqueous extracts gave better growth inhibition compared to the ethanol extracts. Growth inhibition of F. oxysporum was better than that of F. verticillibides, which in turn was significantly better than that of C. orbiculare. Extracts from cloves of A. sativum and leaves of M. oleifera can be said to possess fungitoxic potentials against fungi associated with rot of cucumber. Further work in the field will be needed before credible assertions can be made on their fungitoxicity